1973
DOI: 10.2337/diab.22.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic Modulation of Basal Insulin Secretion in Man

Abstract: In normal men of varying degrees of adiposity, alphaadrenergic blockade (one-hour intravenous infusion with phentolamine, 0.5 mg./min.) produced a 31 ± 23 per cent (mean ± S.D.) increase (n = 6, p < .02) over basal insulin levels whereas beta-adrenergic blockade (one-hour intravenous infusion with propranolol, 0.08 mg./min.) produced a 38 ± 15 per cent decrease (n = 6, p < .002) from basal insulin levels; basal glucose did not change during either type of blockade. Epinephrine (two-hour intraveno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
86
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(100 citation statements)
references
References 0 publications
14
86
0
Order By: Relevance
“…This is not surprising, however, since the effect of catecholamines on glucose levels in vivo is probably due to several actions such as an a-mediated inhibition of insulin secretion [25], increased hepatic glucose production [26] and reduced peripheral insulin sensitivity and responsiveness [2,3]. In this context, it should also be noted that insulin levels were similar before and after surgery.…”
Section: Discussionmentioning
confidence: 87%
“…This is not surprising, however, since the effect of catecholamines on glucose levels in vivo is probably due to several actions such as an a-mediated inhibition of insulin secretion [25], increased hepatic glucose production [26] and reduced peripheral insulin sensitivity and responsiveness [2,3]. In this context, it should also be noted that insulin levels were similar before and after surgery.…”
Section: Discussionmentioning
confidence: 87%
“…Islet innervation of adrenergic nerves has been documented for many years (27). A body of evidence in both animals and humans has demonstrated that sympathetic stimulation induces an inhibition of basal and glucose-stimulated insulin secretion (28,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Originally, antagonism at alpha-adrenoceptors was supposed to be the mechanism of action of the prototypical imidazoline, phentolamine [4,5]. When it became clear that the insulinotropic property of this compound was not due to alpha-antagonism but was related to the presence of an imidazoline moiety [6,7], it was hypothesised that, like other tissues, beta cells express specific imidazoline binding sites [8][9][10].…”
Section: Introductionmentioning
confidence: 99%